(untitled) (Global Journal of Science Frontier Research, 2015)
In the atmosphere many gaseous pollutants like CO, O 3 , NO X and CH 4 are present fluctuates with the atmospheric temperature, relative humidity (RH) and rainfall. The annual average observation of the year 2013 is presented in this paper, which shows the entire monthly average from January to December. Correlation of carbon monoxide (CO), ozone (O 3 ) and oxides of nitrogen (NO X ) has shown negative correlation with temperature, relative humidity and rainfall. In addition to this, methane (CH 4 ) also shows negative correlation with temperature and positive correlation with relative humidity and rainfall. The major fluctuation of temperature and RH was observed in the month of May (increased) whereas, in the month of August rainfall was more fluctuated (decreased).